Barn owls as a biological control agent of rats in paddy fields. - M. N., Hafidzi
The role of barn owls, Tyto alba, in controlling ricefield rats in paddy fields was investigated based on the census of barn owl population, damage census on rice crop and baiting requirements in Selangor, where the barn owl project has been implemented from 1988 to 1997. Rice crop loss due to rat activities before the implementation of the project ranged from 5 to 10%, but this was reduced to less than 1% after that. Monthly occupancy rates and proportion of boxes with eggs and owlets showed that the barn owl population is influenced by the paddy planting stages. It reaches its peak during the period between harvesting and the booting stage of the subsequent crop which also coincides with the rat reproductive cycle.